(untitled) (Iraqi Journal of Civil Engineering, 2012)
The object of this paper was reduced the heat transferred quantities from or to internal building space by covering it’s external walls with many materials, therefore, the researcher build the (1x1x2) m room sample at 3rd floor for building in Baghdad city (L = 33.2 N°), and (1x2)m wall has East orientation , while the other surfaces were insulated by 200 mm styropor sheets, and using Air – Conditioner 0.5 Ton of refrigeration to afford the standard thermal comfort. The researcher found that, the metal sheet painted with thermal plastic paint with 10 mm thermal insulation used as a cover layer for ordinary wall saved 57% from electrical energy consumption in Air-Conditioner, while used that material without insulation layer gives 46.2% , hollow plastic board (for decorative used) gives 42.5% , hollow faced brick with thermal insulation gives 40.22%, solid flooring brick with thermal insulation gives 39.5% , colour metal sheets with air – gap gives 36.4%, asbestos – cement board coated by reflective aluminum paint gives 34%, the ceramic with thermal insulation gives 31.9%, while all the material – marble , porcelene , hallan stone , fiberglass sheets with 10 mm thermal insulation will gives the electrical energy reduction percentage less than 30% .